ESTUDO CONFORMACIONAL DE DERIVADOS DO ÁCIDO FENILACÉTICO EMPREGANDO CÁLCULOS TEÓRICOS E AS ESPECTROSCOPIAS DE RESSONÂNCIA MAGNÉTICA NUCLEAR E INFRAVERMELHO - Levandowski, Mariana Negrelli (2017)
This study presents a theoretical and experimental analysis of the conformational equilibrium of phenylacetic acid and its derivatives, namely: o-fluorophenylacetic, ochlorophenylacetic, o-bromophenylacetic, o-nitrophenylacetic, hydroxyphenylacetic, m-fluorophenylacetic, p-fluorophenylacetic, p-nitrophenylacetic, p-hydroxyphenylacetic, p-mercaptophenylacetic and p-aminophenylacetic. Thetechniques used were computational calculations and nuclear magnetic resonance and infrared spectroscopy.The study made it possible to verify the conformational preference of each compound, determined by their energies and geometries, which were evaluated both for the isolated molecule, at distinct theory levels, and in different solvents, with the IEF-PCM solvation model. By using natural bond orbital calculations, it was possible to identify the main orbital interactions for each conformation. With the total deletion calculations, it was verified that there was a balance between the steric and hyperconjugative effects in the stabilization of the most stable structures. The majority conformers of halogenated compounds in ortho revealed the same spatial orientation between the carbonyl and the benzene ring, similar to that of the phenylacetic acid. In the derivatives, nitro and hydroxylated in ortho, there was the presence of an intramolecular hydrogen bond, but in none of these cases the interaction referred to one of the main conformers. The infrared experiments in solvents of different polarities, allowed the identification of more than one band, enabling the attribution of conformers present in the equilibrium as well as the observation of the same tendency as the one obtained theoretically. The coupling constant 1JCH was evaluated through nuclear magnetic resonance. No significant variation of this constant was observed, showing that the major contribution to the equilibrium is related to the majoritarian conformer, which prevails even with the change in the polarity of the medium, for each compound under evaluation.